1972
DOI: 10.1149/1.2404224
|View full text |Cite
|
Sign up to set email alerts
|

Solution Chemistry and Colloid Formation in the Tin Chloride Sensitizing Process

Abstract: For many years, stannous chloride solutions have been used to prepare surfaces so that they would catalyze deposition from electroless plating solutions. This paper discusses the colloid and solution chemistry of such baths, including the colloid formation, size mediation, and aging processes. The colloid is shown to be nucleated by stannic ions, and mediated by stannous ions. The investigation was carried out primarily using Mössbauer spectroscopy to characterize the materials involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 5 publications
(8 reference statements)
3
50
0
Order By: Relevance
“…Although the current report and the published work of Cohen (7,8) both describe the presence of colloidal particles containing tin (IV), it should be apparent that these are different colloids. These two colloids, although their formulas are not known, result in different chemical and physical characteristics of the final sensitizer solutions.…”
Section: Table II Contact Angle (A) Vs Tetravalent Salt (B) In Sensmentioning
confidence: 68%
See 2 more Smart Citations
“…Although the current report and the published work of Cohen (7,8) both describe the presence of colloidal particles containing tin (IV), it should be apparent that these are different colloids. These two colloids, although their formulas are not known, result in different chemical and physical characteristics of the final sensitizer solutions.…”
Section: Table II Contact Angle (A) Vs Tetravalent Salt (B) In Sensmentioning
confidence: 68%
“…The colloidal particles are a polymerized specie(s) containing tin(IV). In a recent publication, Cohen et al (7,8) proposed a model for the mechanism of conventional sensitizers. In their proposed model, the presence of stannic hydroxide (or hydrated stannic oxide) colloids in bulk solution was invoked as being primarily responsible for the sensitization process.…”
Section: Table II Contact Angle (A) Vs Tetravalent Salt (B) In Sensmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer component of the shell consist of m-hydroxy-bridged Sn(II) and Sn(IV) oligomers which advocate the stabilization of catalytic particle against aggregation over the surface of polymer substrate by the virtue of inherent negative charge and hydrogen bonding interaction with water molecules and it also maintains the state of zerovalent Pd-Sn core required to catalyze the electroless deposition. [19][20][21][22][23] Zabetakis et al reported that the adherence of b-stannic shells are critically important for the catalyzing the activity of the core for metal deposition but adhesion is generally weak and binding with the polymer surface occurs via van der Waals or other non-covalent interaction. 24 Therefore, surface activation was believed to be catalyzed by seeding of Pd(0) on the ber surface, resulting in development of nucleation site for the further deposition of metallic particles.…”
Section: Methodsmentioning
confidence: 99%
“…It has been established, with the aid of MSssbauer spectroscopy, that the sensitizing sites are colloidal particles of Sn +2 and Sn +4 mixed. 24 The colloids form by combined oxidation and hydrolysis in solution and readily adhere to the glass surface. Not only do these sites sensitize the growth of silver-rich films, but, upon exposure to an acidified, aqueous solution of typically 0.1 g/liter PdC12 9 2H20 Sn +2 + Pd +2 ---> Sn *4 + Pd ~ [5] The Pd is an activator or catalyst for electroless deposition of Cu, Ni, and Co. 25 In reality, the effective surface of the silver activator film is very likely to be Ag20.…”
Section: Metals and Nitridesmentioning
confidence: 99%